THE THE DIFFERENCES BETWEEN THE EFFECTIVENESS OF INFRARED INTERVENTION AND PLANTAR FASCIA STRETCH AND INFRARED INTERVENTION AND CALF RAISES TOWARD REDUCTION OF PLANTARIS PAIN OF FEMALE EMPLOYEES IN RAMAYANA BALI MALL WITH HIGH HEELS. - Prabashanti, Ni Nyoman Devi Yani; Andayani, Ni Luh Nopi; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT             The aim of this research is to understand the differences between the effectiveness of infrared intervention and plantar fascia stretch and infrared intervention and calf raises toward reduction of plantar heel pain. This research is an experimental research with pre test and post text two groups design. The sample of this research is 30 people which are divided into two groups.  This result indicates that there is a reduction of pain in each group. In difference test between first and second group by using independent sample t-test the result is  p=0.847 (p> 0.05 ). Based on the result, it can be concluded that infrared intervention and plantar fascia stretch is as good as infrared intervention and calf raises toward reduction of plantaris pain. Keywords : Plantar heel pain, plantar fascia stretch , calf raises , infrared , VAS.